Dual-fiber optical tweezers integrating high-sensitivity structured-light displacement measurement system on fiber end-face - Guofeng Li; Wei Xiong; Haining Feng; Zijian Feng; Tengfang Kuang; Zhechun Lu; Xiang Han; Xin He; Xinlin Chen; Junbo Yang; Guangzong Xiao (Scientific Reports)
Abstract The dual-fiber optical tweezers have become widespread in trapping, assembling, and sensing due to their simple fabrication process and flexible operation. However, the miniaturization and integration of their displacement measurement optical paths remain challenging. Here, we propose and experimentally demonstrate an integration of structured-light displacement (SLD) measurement method tailored for dual-fiber optical tweezers. A key component split-waveplate is integrated onto the fiber end via coating and etching in the SLD method. The etched fiber and another single mode fiber form optical tweezers, which enables to trap particle and measure its position simultaneously without additional optics. More importantly, it demonstrates a superior signal-to-noise ratio after filtering out the trapping field by the etched fiber. Our results demonstrate a displacement sensitivity reaching the 0.1 pm/Hz1/2 level, which surpasses the performance of most results using the quadrant photodiode method. Ultimately, we discussed the possibilities of using two etched fibers to detect displacements in different directions, or integrating this method into a single optical fiber. This method has significant potential applications in precision sensing, contributes to the integration of optical tweezers and fosters the development of lab-on-fiber applications.